Shape Memory Epoxy Foams and Composites: Ribes_foam2 Experiment on Spacecraft "Bion-m1" and Future Perspective. (2015) - Santo, L.; Quadrini, F.; Villadei, W.; Mascetti, G.; Zolesi, V.
Abstract: Shape memory epoxy foams and composites were tested in April 2013, on board the BION-M1 spacecraft through the Soyuz-2 launch vehicle, with the aim to study their behaviour in microgravity for future applications. The on-orbit Ribes_Foam2 experiment consisted in the heating of three samples in various configurations having different shapes (a prototype of actuator, a sheet of composite laminate and parallelepiped) packed on ground, to evaluate the shape recovery capabilities in the space environment. As expected, micro-gravity does not affect the ability of the samples to recover their shape in these configurations but it poses limits for the heating system design because of the difference in heat transfer on earth and on orbit. In this work, the main results of the experiment are discussed. They have provided useful information for the development of actuators and deployable structure, highlighting future perspectives.